Self-Study: Tensions and Growth in Graduate Teaching Assistant Development - Wu, Ching-Hsuan (Central European Journal of Educational Research, 2021)
Graduate Teaching Assistant (GTA) development is an important undertaking for many higher education institutions in the United States. During the GTA preparation process, tensions can arise when the supervisor challenges GTAs by engaging in critical reflection and pushing them to advance their pedagogical skills beyond their comfort zone. Guided by Berry’s (2008) framework of tensions, this self-study aimed to answer the research question: How do tensions that arise during GTA development contribute to the professional growth of teacher educators and GTAs in their teaching? Self-study was the research method, and the data were analyzed using the strategy of inductive analysis and creative synthesis (Patten, 2002). This self-study reports five types of tensions: telling and growth; confidence and uncertainty; safety and challenge; valuing and reconstructing experience; and planning and being responsive. The findings explain how these tensions pushed the supervisor and the GTA to reflect on teacher preparation, manage challenges, and improve teaching. While tensions place teacher educators and novice teachers in uncomfortable positions, this study shows that reflections on and articulation of tensions in collaborative dialogues can help both discover aspects of their teaching that provide opportunities for growth and lead both to transform tensions into teachable moments.